Characteristics of hydrogen and bioflocculant production by a transposon-mutagenized strain of Pantoea agglomerans BH18. (28th December 2016) - Liu, Hongyan; Wang, Hongyu; Qin, Haihua
Abstract: Based on the transposon-mutagenized library of Pantoea agglomerans BH18, the mutant strain 2-103 was obtained using mutant screens for high simultaneous production of hydrogen and bioflocculant. The mutant strain 2-103 was able to grow in medium with 50 μg/mL of kanamycin and could be amplified using Tn7-based transposon PCR amplification in cells from several passages, indicating that the mutant strain 2-103 transposon insertion was stable. The mutant strain 2-103 cell culture from batch experiments with varying initial pH values, glucose concentrations and NaCl concentrations was determined. The result indicated that the optimum initial pH for hydrogen production and bioflocculant activity was 7.0 and 8.0, respectively. The optimal glucose concentration for hydrogen and bioflocculant production was 20 g/L. In addition, the mutant strain 2-103 could produce hydrogen and bioflocculant under marine and fresh culture conditions. The mutant strain 2-103 had the highest production of hydrogen and bioflocculant with (1.55 ± 0.07) mol H2 /mol glucose and (83.7 ± 5.89)% under marine culture conditions, which increased to (1.78 ± 0.08) mol H2 /mol glucose and (93.5 ± 6.24)% under fresh culture conditions. This study found that the mutant strain 2-103 has the ability to produce hydrogen and bioflocculant within a range of initial pH values, glucose and NaCl concentrations, which is beneficial for the improvement of cost-effective bio-treatment processes. Highlights: The strain 2-103 was a transposon-mutagenized strain of Pantoea agglomerans BH18. The mutant strain 2-103 could simultaneously produce hydrogen and bioflocculant. H2 yield and bioflocculant activity were 1.55 ± 0.07 and 83.7 ± 5.89 in marine condition. Strain 2-103 produced hydrogen and bioflocculant at NaCl concentration (0–60 g/L).